The infinite possibilities of RNA therapeutics. (31st August 2021) - Mollocana-Lara, Evelyn C; Ni, Ming; Agathos, Spiros N; Gonzales-Zubiate, Fernando A
Abstract: Although the study of ribonucleic acid (RNA) therapeutics started decades ago, for many years, this field of research was overshadowed by the growing interest in DNA-based therapies. Nowadays, the role of several types of RNA in cell regulation processes and the development of various diseases have been elucidated, and research in RNA therapeutics is back with force. This short literature review aims to present general aspects of many of the molecules currently used in RNA therapeutics, including in vitro transcribed mRNA (IVT mRNA), antisense oligonucleotides (ASOs), aptamers, small interfering RNAs (siRNAs), and microRNAs (miRNAs). In addition, we describe the state of the art of technologies applied for synthetic RNA manufacture and delivery. Likewise, we detail the RNA-based therapies approved by the FDA so far, as well as the ongoing clinical investigations. As a final point, we highlight the current and potential advantages of working on RNA-based therapeutics and how these could lead to a new era of accessible and personalized healthcare.